Characteristics of educational sciences research activity in European post-socialist countries in the period 1996 to 2013: Content analysis approach. (July 2019) - Bouillet, Dejana; Jokić, Maja
In European post-socialistic countries or more commonly known as Central and Eastern Europe (CEE) countries, regardless of their differences and specifics, the common communist and post-communist legacies in the field of educational sciences are still recognisable. The aim of this article is to explore research activity in the educational sciences in 15 CEE countries: 11 EU member states and 4 from the former Yugoslav Republic in the period from 1996 to 2013. The purpose of this research is to recognise the specificity and dynamics of subject and content issues, and development of methodological approaches in the educational science research. The sample consists of abstracts of 2, 395 papers by CEE authors published in 265 journals indexed in Scopus between 1996 and 2013. Content analysis was applied, where the abstracts were grouped into specifically created categories describing the content and methods of the paper and analysed on the basis of two criterion variables – CEE and non-CEE or international journals. The χ 2 test showed that the field of educational sciences in 15 European post-socialist countries changed over time in terms of quantity, content and methods, becoming more expansive and diverse, which is recognisable in papers published both in international and in CEE journals.